O TRUDNOŚCIACH GLOTTODYDAKTYKÓW Z KONCEPTUALIZACJĄ POJĘCIA ŚWIADOMOŚCI INTERKULTUROWEJ. REFLEKSJA METAGLOTTODYDAKTYCZNA - Griso, Grażyna Małgorzata (Neofilolog, 2019)
With its focus on foreign language teaching/ learning as the subject of study, glottodidactics belongs to empirical sciences which not only refer to the reality perceived with the senses but also necessitates empirical verification. Glottodidactics, being in the development phase and striv-ing to consolidate its status, requires relative consistency in its use of key terms. According to researchers representing the intercultural approach, cultural awareness is such term. For an autonomy-seeking science, preci-sion and relative coherence in defining concepts are necessary not only in the external dimension, but also in the consolidation of knowledge which occurs in the process of scientific communication. Reviewing the literature on glottodidactics, the article shows the current state of research in the field of conceptualizing cultural awareness.